2018
DOI: 10.1186/s41479-018-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased relative risk of pneumococcal pneumonia during the last decade, a nested case-control study

Abstract: BackgroundStreptococcus pneumoniae (SP) is one of the most common pathogens of Community-Acquired Pneumonia (CAP), but recent reports suggest that its incidence may be declining in relation to the use of the conjugate 13-valent pneumococcal vaccine in children. We compared the result of the immunochromatographic SP urinary antigen test (SPUAT) and clinical outcomes in patients with CAP admitted in two periods of time: 2001–2002(CAP1) and 2015–2016(CAP2).MethodsThis was a matched nested case-control study of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Adult and at-risk pneumococcal and influenza vaccination data were obtained from [ 5 ] and: Andorra [ 108 ]; Argentina [ 109 , 110 ]; Belgium [ 111 ]; Brazil [ 112 ]; Central and Eastern Europe [ 113 ]; Denmark [ 114 , 115 ]; European nations [ 85 , 116 , 117 , 118 , 119 ]; Europe and Gulf nations [ 120 ]; Germany [ 121 ]; Gulf nations [ 122 , 123 ]; Hong Kong [ 124 ]; Hungary [ 125 ]; Iceland [ 126 ]; Ireland [ 127 ]; Israel [ 128 ]; Latin America [ 129 ]; Mexico [ 130 , 131 ]; New Zealand [ 132 ]; Poland [ 133 ]; Qatar [ 134 ]; San Marino [ 135 ]; Singapore [ 136 ]; Slovenia [ 137 ]; South Africa [ 138 ]; Sweden [ 139 ]; Switzerland [ 140 , 141 , 142 ]; Taiwan [ 143 , 144 , 145 ]; Turkey [ 146 , 147 , 148 ]; and U.K. [ 149 ]. All of these data are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Adult and at-risk pneumococcal and influenza vaccination data were obtained from [ 5 ] and: Andorra [ 108 ]; Argentina [ 109 , 110 ]; Belgium [ 111 ]; Brazil [ 112 ]; Central and Eastern Europe [ 113 ]; Denmark [ 114 , 115 ]; European nations [ 85 , 116 , 117 , 118 , 119 ]; Europe and Gulf nations [ 120 ]; Germany [ 121 ]; Gulf nations [ 122 , 123 ]; Hong Kong [ 124 ]; Hungary [ 125 ]; Iceland [ 126 ]; Ireland [ 127 ]; Israel [ 128 ]; Latin America [ 129 ]; Mexico [ 130 , 131 ]; New Zealand [ 132 ]; Poland [ 133 ]; Qatar [ 134 ]; San Marino [ 135 ]; Singapore [ 136 ]; Slovenia [ 137 ]; South Africa [ 138 ]; Sweden [ 139 ]; Switzerland [ 140 , 141 , 142 ]; Taiwan [ 143 , 144 , 145 ]; Turkey [ 146 , 147 , 148 ]; and U.K. [ 149 ]. All of these data are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The authors indicated that routine childhood PCV13 vaccination, which was initiated in 2012, may have also contributed. 18 A systematic review of studies published on CAP etiology in Asia, concluded that while S. pneumoniae was the most common cause, it was of relatively less importance than that found in western studies. 19 In contrast to this, a literature review evaluating the etiology (and antibiotic management) of CAP in Europe reported on 33 published studies that recorded pathogens and noted that the pneumococcus was the most commonly isolated pathogen and was identified in between 12.0 and 85.0% of the patients in the different regions.…”
mentioning
confidence: 99%